Physicochemical properties and acceptability study of high energy cereal bar made from Malaysian puff glutinous rice with halal ingredients - Hassan C.Z.; Jamal A.F.; Kal-kausar M.A.; Ismail S. (Josip Juraj Strossmayer University of Osijek, Faculty of Food Technology Osijek, 2024)
Indexed by Scopus